Cost-Deadline Based Task Scheduling in Cloud Computing - Himani; Sidhu, Harmanbir Singh (2015 Second International Conference on Advances in Computing and Communication Engineering, 2015)
Cloud computing is a nascent technology which widely spreads among researchers. It provide users with infrastructure, platform and software as amenity which is effortlessly accessible via Internet. In cloud computing, there are numerous tasks needs to be executed by the existing resources to attain best performance, shortest response time, minimal total time for completion, achieve deadline, utilization of resources etc. Scheduling is a complicated task in cloud computing environment where the aim is to schedule the tasks effectively so as to reduce the turnaround time and improve overall performance. Due to these dissimilar objectives, we need to design, develop a noble scheduling strategy to outperform proper division of tasks on virtual machines. Recently existing scheduling algorithm may work proficiently in some perspective. But they are unable to achieve deadline of task and attain maximum profit. In this paper, new mechanism is proposed which take care of deadline and cost, then scheduled the task according to need. Based on the concept of space-shared scheduling policy, this work presents Cost-deadline Based (CDB) task scheduling algorithm to schedule tasks with Cloud-sim by taking into account several parameters including task profit, task penalty, throughput, provider profit, user loss.